Prophage Activation in the Intestine: Insights Into Functions and Possible Applications - Hu, Jie; Ye, Hao; Wang, Shilan; Wang, Junjun; Han, Dandan (Frontiers in Microbiology, 2021)
Prophage activation in intestinal environments has been frequently reported to affect host adaptability, pathogen virulence, gut bacterial community composition, and intestinal health. Prophage activation is mostly caused by various stimulators, such as diet, antibiotics, some bacterial metabolites, gastrointestinal transit, inflammatory environment, and quorum sensing. Moreover, with advancements in biotechnology and the deepening cognition of prophages, prophage activation regulation therapy is currently applied to the treatment of some bacterial intestinal diseases such as Shiga toxin-producing Escherichia coli infection. This review aims to make headway on prophage induction in the intestine, in order to make a better understanding of dynamic changes of prophages, effects of prophage activation on physiological characteristics of bacteria and intestinal health, and subsequently provide guidance on prophage activation regulation therapy.